Development and characterization of polylactic acid/starch biocomposites - From melt blending to preliminary life cycle assessment - Baniasadi, Hossein; Äkräs, Laura; Madani, Zahra; Silvenius, Frans; Fazeli, Mahyar; Lipponen, Sami; Vapaavuori, Jaana; Seppälä, Jukka (Elsevier, 2024)
This study presents a comprehensive analysis encompassing melt blending, characterization, life cycle assessment (LCA), and 3D printing of a range of polylactic acid (PLA)/starch biocomposites, with starch content varying from 0 to 50 wt%. To enhance compatibility between the starch particles and the PLA matrix, we utilized a solvent-free method to graft N-octadecyl isocyanate (ODI) molecules onto the surface of the starch particles, resulting in ODI-g-starch, which yielded several improved properties. Notably, toughness and elongation at break improved by approximately 170 % and 300 %, respectively. Moreover, the crystallinity increased from 11.6 % in plain PLA to 30.1 %, suggesting that the uniform dispersion of ODI-g-starch particles acted as nucleating sites for the crystallization of PLA chains. Additionally, viscosity decreased significantly with the introduction of ODI-g-starch particles, indicating their plasticizing effect, thereby enhancing the processability and ease of fabrication of the biocomposite. Crucially, our LCA analysis revealed a significant reduction in the carbon footprint of these biocomposites, up to 18 % and 63 %, compared to plain PLA and selected fossil-based plastics, respectively, upon the incorporation of ODI-g-starch. In summary, our research introduces the newly developed PLA/starch biocomposites as a sustainable and eco-friendly alternative to commercially available plain PLA and specific fossil-based plastics.
Keywords: polylactic acid; starch; biocomposite; life cycle assessment; 3D printing